Recent advances in nanoparticles associated ecological harms and their biodegradation: Global environmental safety from nano-invaders. Issue 5 (October 2021) - Ahmed, Temoor; Noman, Muhammad; Manzoor, Natasha; Ali, Shafaqat; Rizwan, Muhammad; Ijaz, Munazza; Allemailem, Khaled S.; BinShaya, Abdulkarim S.; Alhumaydhi, Fahad A.; Li, Bin
Abstract: In recent years, engineered nanomaterials have gained enormous attention due to their beneficial applications in various areas of science including industrial, environmental and life sciences. Importantly, the use of nanotechnology in agriculture will result in the release of nanoparticles (NPs) into the environment and may contaminate the food chain by entering into the plant system. However, many barriers to implementation must be addressed for technology to be adopted, including safety concerns, consumer acceptance and efficient delivery at field scale. Moreover, NPs interactions with the ecosystem and their toxicity in living systems have become a serious global concern. Additional intricate knowledge is still required about the long-term toxicological fate of NPs released in the environment and their biodegradation. The objective of this review is to provide the various sources of NPs release in the environment, exposure routes and their toxicity in agro-environment subsystems along with potential health risks to human. It also explores the possible mechanism of NPs biodegradation, emerging developments, and potential pitfalls into the research on biodegradable NPs to achieve environmental safety as well as global food security and sustainability. Graphical Abstract: ga1 Highlights: Fate and transformation pathways of nanoparticles (NPs) in distinct environment system. NPs pollution has perturbed the environment to pose serious health hazards. Toxicity of NPs to plant, microorganisms and human health have become a global concern. This review provides possible mechanism of NPs biodegradation in a eukaryotic cell. This review will be a valuable addition in the field of nanotechnology to develop eco-friendly and biodegradable NPs.